All the Wisdom of the East : Studies in Near Eastern Archaeology and History in Honor of Eliezer D. Oren - Gruber, Mayer Irwin; Aḥituv, Shmuel; Lehmann, Gunnar; Ṭalshir, Tsiporah (2012)
All the Wisdom of the East is a tribute to Professor Eliezer D. Oren, a multi-faceted archaeologist of the Levant and its cultural connections with the Aegean, renowned student of the Negev and Northern Sinai, and founder of the Archaeological Division in the Department of Bible, Archaeology and Ancient Near Eastern Studies at Ben-Gurion University of the Negev, Beer-Sheva. The book includes an appreciation of the honoree and a list of his numerous publications. Thirty-nine scholars, colleagues and former students from Israel, Europe, the United States of America and New Zealand have contributed original studies in English (22), German (1) and Hebrew (5) to this volume. The spectrum of their papers covers various fields and periods, from pre-history to the Roman Period, from Egypt to the Aegean and the Western Mediterranean, from pottery to art, epigraphy and history. The book thus offers a wealth of knowledge and information of importance to anyone interested in the Ancient Near East.